PENGARUH KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR MAHASISWA AKUNTANSI DENGAN VARIABEL MODERATING KEPERCAYAAN DIRI - Marieta Ariani (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2013)
Education was one of the way human increased their welfare. It's also power integrity which effected by emosion, ethics, trust and etc. In Framework of Development of Accounting Education Research which promulgated by the American Accounting(AAA), state that there were special research needs for accounting education. This research is evaluate the influence of emotional intelligenceto achievement learning accounting with self confidence as moderating variable.The research population were all of student accounting in Faculty Economic of Trisalai University. Samples were collected by used purposive sampling method, so acquired about 170 students. The research used regression analysis to analyse the data.. The result of research revealed that emotional intelligence and self confidence as modarating variable has no significant effect to achievement learning accounting.